Paediatric migraine with visual hallucination auras appearing in the form of a human body. Issue 12 (2nd December 2019) - Akiyama, Osamu; Kondo, Akihide; Akiyama, Iwao
Abstract : The most common type of migraine aura is multifaceted visual aura, such as scintillating scotoma or geometrical patterns, visual hallucinations in which a physical body is extremely rare. We report a paediatric case of migraine in which visual hallucinations appeared as auras in the form of a human body. The patient was an 11-year-old girl suffering from migraine with curious visual aura. The auras were atypical visual hallucinations that were sometimes accompanied by auditory hallucinations. Approximately 5–20 min before the headache, the patient would see a middle-aged man wearing sunglasses in her field of vision. Acetaminophen (10 mg/kg) and Japanese herbal medicine administered when necessary effectively treated the headaches. Finally, the patient was no longer complaining of her hallucination auras. Although the pathophysiology of migraines accompanied by auras is unclear, it appears that cerebral blood flow and cortical spreading depression are involved in auras.